2015
DOI: 10.1289/ehp.1408660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Diet Intervention on Pesticide Exposures in Young Children Living in Low-Income Urban and Agricultural Communities

Abstract: BackgroundRecent organic diet intervention studies suggest that diet is a significant source of pesticide exposure in young children. These studies have focused on children living in suburban communities.ObjectivesWe aimed to determine whether consuming an organic diet reduced urinary pesticide metabolite concentrations in 40 Mexican-American children, 3–6 years of age, living in California urban and agricultural communities.MethodsIn 2006, we collected urine samples over 16 consecutive days from children who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 35 publications
9
82
0
3
Order By: Relevance
“…Likewise, systematic reviews consistently conclude that organic foods are less likely than conventional food samples to have detectable pesticide residue (7,91,99). Controlled feeding experiments in children and adults have confirmed that consumption of organic food resulted in lower urinary concentrations of pesticide metabolites than consumption of conventional alternatives (16,26,67,84). These studies and a study that estimated dietary pesticide exposure (25) provide convincing evidence that consumption of organic foods reduces the exposure to synthetic pesticide metabolites.…”
Section: Pesticide Residues In Organic and Conventionally Produced Foodmentioning
confidence: 84%
“…Likewise, systematic reviews consistently conclude that organic foods are less likely than conventional food samples to have detectable pesticide residue (7,91,99). Controlled feeding experiments in children and adults have confirmed that consumption of organic food resulted in lower urinary concentrations of pesticide metabolites than consumption of conventional alternatives (16,26,67,84). These studies and a study that estimated dietary pesticide exposure (25) provide convincing evidence that consumption of organic foods reduces the exposure to synthetic pesticide metabolites.…”
Section: Pesticide Residues In Organic and Conventionally Produced Foodmentioning
confidence: 84%
“…Indeed, several short-term intervention studies have showed that young children's exposure to organophosphate pesticides, the most widely used pesticides in agriculture sectors (Chen et al, 2009; Sharma et al, 2010; Wang et al, 2008), is primarily from diet (Bradman et al 2015; Lu et al, 2008, 2006). In addition, although some organochlorine pesticides such as hexachlorobenzene have been banned from use in U.S. for 50 years, their residues persist in soil and water because of their long half-lives and thus they may still affect human health (Jones and de Voogt, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary metabolites were significantly lower when an organic diet was consumed. Children residing in the agricultural community showed a lower decrease in dimethyl metabolites than those in a suburban community (Bradman et al 2015). It may be that the background noise in an agricultural community (e.g., spray drift) has an effect on all children in an agricultural community (Richter ED et al 2015).…”
Section: Discussionmentioning
confidence: 99%